Regulation of pituitary stem cells by epithelial to mesenchymal transition events and signaling pathways - Cheung, Leonard Y. M. (2017)
The anterior pituitary gland is comprised of specialized cell-types that produce and secrete polypeptide hormones in response to hypothalamic input and feedback from target organs. These specialized cells arise from stem cells that express SOX2 and the pituitary transcription factor PROP1, which is necessary to establish the stem cell pool and promote an epithelial to mesenchymal-like transition, releasing progenitors from the niche. The adult anterior pituitary responds to physiological challenge by mobilizing the SOX2-expressing progenitor pool and producing additional hormone-producing cells. Knowledge of the role of signaling pathways and extracellular matrix components in these processes may lead to improvements in the efficiency of differentiation of embryonic stem cells or induced pluripotent stem cells into hormone producing cells in vitro. Advances in our basic understanding of pituitary stem cell regulation and differentiation may lead to improved diagnosis and treatment for patients with hypopituitarism.